Prognostic biomarker NEIL3 and its association with immune infiltration in renal clear cell carcinoma - Sun, Xiaomei; Liu, Pengfei (Frontiers in Oncology, 2023)
Background: Kidney renal clear cell carcinoma (KIRC) is a malignant tumor with a high degree of immune infiltration. Identifying immune biomarkers is essential for the treatment of KIRC. Studies have identified the potential of NEIL3 to modulate the immune microenvironment and promote tumor progression. However, the role of NEIL3 in KIRC remains uncertain. This study was to investigate the effect of NEIL3 on the prognosis and immune infiltration of patients with KIRC. Methods: The expression of NEIL3 in KIRC was investigated using TCGAand GEOdatabases. Cox regression analysis was used to examine the relationship between NEIL3 expression and clinicopathological variables and survival. Furthermore, Gene Set Cancer Analysis (GSCA) was applied to study the impact of NEIL3 methylation on the outcome of KIRC. Biological processes and signaling pathways related to NEIL3 expression were identified by GO and GSEA analysis. In addition, immuno-infiltration analysis was conducted via CIBERSORT, ssGSEA, and TISIDB databases. Results: NEIL3 was overexpressed in KIRC and significantly correlated with histologic grade, pathologic stage, T stage, M stage, and vital status of KIRC patients (P < 0.001). NEIL3 expression was associated with worse outcomes. Univariate and multivariate Cox analysis showed NEIL3 may be an indicator of adverse outcomes in KIRC. GSEA analysis revealed that NEIL3 may be implicated in signaling pathways including cell cycle, DNA replication, mismatch repair, P53 signaling pathway, and antigen processing and presentation. In addition, immune infiltration analysis showed a positive correlation between NEIL3 expression and multiple immune cells (activated CD8 T cells, DC, MDSC, Tfhs, and Tregs) and immunoinhibitors (PD1, CTLA4, LAG3, TIGHT, IL10, and CD96). Conclusion: NEIL3 is a potential independent biomarker of KIRC and relevant to immune infiltration.